Fostering International Student Success in Higher Education - Johnson, Rachel Sherman (Journal of International Students, 2015)
As the number of international students enrolling in English-dominant higher education continues to rise, this timely book offers university faculty and staff members useful suggestions for responding effectively to the unique needs and challenges of this growing student population. At the same time, though the primary focus is on course design and classroom practice, the book also advocates for international students, noting that they are intellectual, cultural, and linguistic assets to their universities. Shapiro, Farrelly, and Tomaš, all veteran teachers with many years of experience working directly with international students, present a holistic framework for how to support international students’ academic development and their integration into the broader campus community.